Hydrodynamic testing of flexible profiles for a vertical axis turbine - Zeiner-Gundersen, D.H.; Zeiner-Gundersen, S.A.S. (Прикладна гідромеханіка, 2015)
Hydrodynamic turbine functionality depends on the ability of the individual profiles to capture the water energy efficiently during rotation. Here, we describe a unique flexible profile design based on hydrodynamic thrust characteristics inspired by swimming and flying creatures. The concept was based on a flexible double cambered profile that would have a relatively high lift to drag ratio independent of the rotational azimuth position in a vertical axis hydrodynamic turbine application. In order to establish the design of a profile to be implemented into a vertical axis turbine, several different flexible profile models were tested in a cavitation tunnel with controlled water flow dynamics, and their lift, drag, and momentum characteristics were established. Гидродинамическая функциональность турбины зависит от способности каждого профиля захватывать энергию воды во время вращения. Здесь мы описываем уникальный дизайн гибкого профиля, основанный на характеристиках гидродинамической тяги, подобной используемой плавающими и летающими живыми существами. Концепция основывается на гибком профиле двойной кривизны, который имеет относительно высокое отношение подъемной силы к силе сопротивления независимо от положения по углу вращения, в применении для гидродинамических турбин с вертикальной осью. Гiдродинамiчна функцiональнiсть турбiни залежить вiд властивостi кожного профiля захоплювати енергiю води пiд час обертання. Ми описуємо унiкальний дизайн гнучкого профiля, який базується на характеристиках гiдродинамiчної тяги, подiбної до тої, яка використовується плаваючими та лiтаючими живими iстотами. Концепцiя полягає у використаннi гнучкого профiля подвiйної кривизни, який має вiдносно високе вiдношення пiднiмальної сили до сили опору незалежно вiд позицiї по куту обертання, в застосуваннi для гiдродинамiчних турбiн з вертикальною вiссю. We thank Jan Hallander and Torleif Johansson at SSPA (Chalmers University, Gøteborg, Sweden) for assistance with the profile design and use of their cavitation tunnel equipment. We also thank Kinetic Energy a.s. (Oslo, Norway) and the Norwegian Government Renewable Energy Program for financial support, and Dr. Carol Wenzel (Vancouver, Canada) for editing.